2019
DOI: 10.1038/s41386-019-0521-6
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Widespread white matter microstructural abnormalities in bipolar disorder: evidence from mega- and meta-analyses across 3033 individuals

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For instance, correlations of schizophrenia versus control deep brain structure effect size profiles based on three independent reports -the ENIGMA Schizophrenia Working Group, 51 Cognitive Genetics Collaborative Research Organization (COCORO), 86,87 and a third independent cohort 11 -showed correlations of about 0.98; for review see. 88 Similarly, case-control fractional anisotropy effect sizes based on ENIGMA 47,73,74 and COCORO 89 r = 0.47); for review see. 32 These findings suggest that large metaand mega-analyses can generate reproducible structural image profiles for neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, correlations of schizophrenia versus control deep brain structure effect size profiles based on three independent reports -the ENIGMA Schizophrenia Working Group, 51 Cognitive Genetics Collaborative Research Organization (COCORO), 86,87 and a third independent cohort 11 -showed correlations of about 0.98; for review see. 88 Similarly, case-control fractional anisotropy effect sizes based on ENIGMA 47,73,74 and COCORO 89 r = 0.47); for review see. 32 These findings suggest that large metaand mega-analyses can generate reproducible structural image profiles for neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For their initial studies, the SZ, BD, and MDD groups used the meta‐analytic method, where each site analyses their own data, and a leading site conducts the meta‐analysis based on each site's results. The 22q11DS group was able to conduct mega‐analyses, which pooled data from all sites for combined analyses while statistically adjusting for effects of scanner (site) 46–49 . Both analysis approaches, also referred to as two‐stage and one‐stage meta‐analyses in the statistical literature, 50 have advantages and disadvantages; for a review and a comparison, see Schmaal et al 29 …”
Section: Working Group Study (Author Year) Cohort N Age Range (Years)...mentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, the resolution of the fMRI images is sub‐optimal (3.75 × 3.75 × 4.55 mm) compared to the newer multi‐band sequences (2–3 mm isotropic). In addition, there are some existing large N datasets, for example, ENIGMA (Favre et al, ; Hoogman et al, ; van Velzen et al, ), 10 K in 1 day (van den Heuvel et al, ) and morphometric similarity networks (Seidlitz et al, ), which introduce several new network features that can be used to investigate age‐related variations in both healthy as well as disease.…”
Section: Discussionmentioning
confidence: 99%